Analysis of clinical and imaging features and prognosis of patients positive for Tropheryma whipplei detected by nanopore sequencing of bronchoalveolar lavage fluid - Song, Chang; Zhao, Chun-Yan; Yu, Mei; Jiang, Chang-Yue; Qiang, Hang-Biao; Liu, Ren-Hao; Yang, Xiao-Mei; Xie, Zhou-Hua; Zhu, Qing-Dong (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundTo probe into the application value of nanopore sequencing in patients suffering from positive Tropheryma whipplei (TW), analyze their clinical features, imaging manifestations, and treatment prognosis, and provide new evidence for the diagnosis and treatment of Whipple’s disease.MethodsThis study retrospectively analyzed 2,137 samples subjected to nanopore sequencing at the Fourth People’s Hospital of Nanning. Among them, 14 bronchoalveolar lavage fluid (BALF) samples were positive for TW. Patients were divided into a high-sequence group (100) and a low-sequence group (≤100) in accordance with the TW sequence counts. The clinical features, laboratory indicators, imaging manifestations, and treatment prognosis of these two groups were compared and analyzed in an all-round manner.ResultsThe levels of C-reactive protein (CRP) and lactate dehydrogenase (LDH) in the high-sequence group were strikingly higher than those in the low-sequence group (P < 0.05). Radiologically, TW pneumonia mostly presented as patchy shadows, ground-glass opacities, and bronchiectasis, which highly overlapped with the imaging features of tuberculosis or interstitial pneumonia. With respect to treatment, 85.7% of the 14 patients exhibited symptomatic improvement subsequent to antibiotic treatment. Fluoroquinolones and combination therapy regimens demonstrated satisfactory efficacy, but patients suffering from severe conditions or advanced age may require an extended treatment course.ConclusionThe imaging manifestations of TW pneumonia are not only non-specific but also have been frequently mistaken with other pulmonary diseases. Notwithstanding the fact that fluoroquinolones and combination therapy regimens hold clinical relevance in the management of Whipple’s disease, tailored adjustments to treatment plans are crucial based on individual patient circumstances.